The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1016/j.tet.2013.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Use of a palladium(II)-catalyzed oxidative kinetic resolution in synthetic efforts toward bielschowskysin

Abstract: Progress toward the cyclobutane core of bielshowskysin is reported. The core was thought to arise from a cyclopropane intermediate via a furan-mediated cyclopropane fragmentation, followed by a 1,4-Michael addition. The synthesis of the cyclopropane intermediate utilizes a Suzuki coupling reaction, an esterification with 2-diazoacetoacetic acid, and a copper catalyzed cyclopropanation. An alcohol intermediate within the synthetic route was obtained in high enantiopurity via a highly selective palladium(II)-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…31 In 2013, Stoltz et al reported the synthesis of a key intermediate in the synthesis of the naturally occurring anti-cancer agent bielschowskysin based on a palladium-catalysed oxidative kinetic resolution performed under oxygen atmosphere. 32 As shown in Scheme 12, the treatment of a racemic functionalised secondary alcohol by a combination of 5 mol % of Pd(nbd)Cl 2 and 20 mol% of (À)-sparteine in toluene at 80 C led to the almost enantiopure (3R,5S)-alcohol (>95% ee) with a high selectivity factor (s ¼ 23) along with the corresponding (3S)-ketone in 57% conversion.…”
Section: Palladium-catalysed Oxidative Kinetic Resolutions Of Secondamentioning
confidence: 99%
“…31 In 2013, Stoltz et al reported the synthesis of a key intermediate in the synthesis of the naturally occurring anti-cancer agent bielschowskysin based on a palladium-catalysed oxidative kinetic resolution performed under oxygen atmosphere. 32 As shown in Scheme 12, the treatment of a racemic functionalised secondary alcohol by a combination of 5 mol % of Pd(nbd)Cl 2 and 20 mol% of (À)-sparteine in toluene at 80 C led to the almost enantiopure (3R,5S)-alcohol (>95% ee) with a high selectivity factor (s ¼ 23) along with the corresponding (3S)-ketone in 57% conversion.…”
Section: Palladium-catalysed Oxidative Kinetic Resolutions Of Secondamentioning
confidence: 99%
“…[17] Isolated in 2004 from a Caribbean coral, 26 was found to possesses potent anticancer activity. [18] The simplified scaffold of 27 was chosen as a model system.…”
Section: Use Of Donor–acceptor Cyclopropanes As Intermediates In Natumentioning
confidence: 99%
“…The Stoltz laboratory continued to investigate the strategy of cyclopropane fragmentation en route to larger carbocyclic rings in their approach toward the total synthesis of bielschowskysin ( 26 , Scheme 6). [17] Isolated in 2004 from a Caribbean coral, 26 was found to possesses potent anticancer activity. [18] The simplified scaffold of 27 was chosen as a model system.…”
Section: Use Of Donor–acceptor Cyclopropanes As Intermediates In Natumentioning
confidence: 99%
“…Hexacyclic natural product 1 is arguably one of the most complex furanocembranoids known to date, as it features an unprecedented cis ‐fused tricyclo[9.3.0.0 2,10 ]tetradecane ring system and 11 stereogenic centers . Numerous groups including our own have communicated efforts towards the total synthesis of bielschowskysin . Although the synthesis of the natural product has not been accomplished yet, our contribution relying on non‐photochemical and photochemical strategies resulted in several advanced intermediates containing the crucial stereogenic center, the cyclobutane moiety, and fully substituted southern as well as northern hemispheres of the target molecule , .…”
Section: Introductionmentioning
confidence: 99%